Ultrahigh Electrical Conductivity of Graphene Embedded in Metals. (27th February 2019) - Cao, Mu; Xiong, Ding‐Bang; Yang, Li; Li, Shuaishuai; Xie, Yiqun; Guo, Qiang; Li, Zhiqiang; Adams, Horst; Gu, Jiajun; Fan, Tongxiang; Zhang, Xiaohui; Zhang, Di
Abstract: Highly efficient conductors are strongly desired because they can lead to higher working performance and less energy consumption in their wide range applications. However, the improvements on the electrical conductivities of conventional conductors are limited, such as purification and growing single crystal of metals. Here, by embedding graphene in metals (Cu, Al, and Ag), the trade‐off between carrier mobility and carrier density is surmount in graphene, and realize high electron mobility and high electron density simultaneously through elaborate interface design and morphology control. As a result, a maximum electrical conductivity three orders of magnitude higher than the highest on record (more than 3, 000 times higher than that of Cu) is obtained in such embedded graphene. As a result, using the graphene as reinforcement, an electrical conductivity as high as ≈117% of the International Annealed Copper Standard and significantly higher than that of Ag is achieved in bulk graphene/Cu composites with an extremely low graphene volume fraction of only 0.008%. The results are of significance when enhancing efficiency and saving energy in electrical and electronic applications of metals, and also of interest for fundamental researches on electron behaviors in graphene. Abstract : Ultrahigh electrical conductivity ≈3000 times higher than that of Cu is realized in graphene embedded in metals . As a result, the corresponding graphene/Cu composites show an electrical conductivity significantly higher than that of Ag. Such graphene/metal interactions provide a unique platform to explore electron behaviors in graphene, and the results open up new opportunities for graphene's applications.